Oracle of phytic acid in dental panacea - Insight into properties, therapeutic effect, regeneration, materials interaction and oral physiology - Ummey Salma; C. Pushpalatha; SV. Sowmya; Dominic Augustine; Ahmed Alamoudi; Bassam Zidane; Nassreen Hassan Mohammad Albar; Shilpa Bhandi (Elsevier, 2024)
Phytic acid (inositol hexaphosphate/IP6) is a versatile chemical that is abundant in nature and is required for a variety of biological processes. It is harnessed in a wide range of fields, including drug discovery, daily supplies, chemical industries, medicine, and dentistry. IP6 is becoming increasingly popular in dentistry, with promising results. Several properties, such as cariostatic ability, beneficial impact on enamel disintegration, and anti-plaque, anti-tartar, and dental adhesive-forming properties, have been investigated thus far. Due to many constraints in the literature, there was a point in time when IP6 received less attention, which impacted knowledge in this field. Nevertheless, the positive outcomes of the flourishing of IP6 have recently been reconsidered from a number of papers that have improved our understanding of its modes of action in the aforementioned applications. The role of phytic acid in refining the properties and manoeuvring of dental resources is being investigated in novel endeavors in treating diseases of pulp and tissues supporting tooth structure, but to show its novel therapeutic potential, more precisely calibrated clinical trials are needed. This review examines and discusses the various uses proposed in the literature, as well as the applications of IP6 in dentistry.